Metode Nilai Jual Relatif Sebagai Dasar Penentuan Harga Pokok Produk Bersama - Megawati Megawati; Maryani Maryani; Rusmianto Rusmianto (Politeknik Negeri Lampung, 2018)
The objective of this study is to know: (1) the influence of BPD Knowledge on budgets on village financial oversight (APBDesa); (2) the influence of interaction of Community participation on the relationship between knowledge of BPD on budget and village financial oversight (APBDesa); (3) The Influence of Public Policy Transparency Interaction on the relationship between knowledge of BPD on budgets and village financial oversight (APBDesa) and (4) Influence of BPD Knowledge interaction on budget, community participation, and transparency of public policy towards village financial oversight (APBDesa). This research was conducted by using the members of the Village Consultative Board (BPD) villages in Waysulan Sub-district, South Lampung Regency (8 Villages) as its object. The hypothesis in this research was tested by using multiple analysis (multiple regression).Â The data processing is done with the help of SPSS statistical application. Hypothesis testing performed after multiple regression models are used free of violation of classical assumptions, so that the test results can be interpreted appropriately. The conclusions can be drawn is that the knowledge of village consultative bodies (BPD) has a significant positive effect on the level of village financial oversight, while public participation, accountability, and transparency of public policy do not affect the relationship between the knowledge of members of village consultative bodies (BPD) these three variables (public participation, accountability, and transparency of public policy) directly affect the level of oversight of village financial management.Key words: Village Consultative Board (BPD), Participation, Knowledge of BPD, VillageÂ financial supervision, Transparency.